THEORETICAL AND METHODOLOGICAL ASPECTS OF THE ANALYSIS AND EVALUATION OF THE MARKETING ACTIVITY OF THE ENTERPRISE IN THE PROCESS OF STRATEGIC MARKETING DECISION-MAKING - Yaneva, Ph. D. Dilyana Emcheva (Revista Inclusiones, 2021)
Knowledge and application of tools for complex analysis and evaluation of the results of the company's marketing activities can be used as a strategic weapon in the competitive struggle. In this regard, the article presents some basic concepts, models, techniques and indicators for the study of marketing performance and its main perspectives. Emphasis is placed on the importance of methodology in the process of strategic marketing decision-making and overall corporate development.